PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN MEDIA GAMBAR BERSERI TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN TEKS NARASI SISWA SEKOLAH DASAR - Nurirpansyah; Hilman Hilmawan; Ilham; Ihsan M Algina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low narrative text reading comprehension ability among elementary school students, as evidenced by their difficulties in understanding reading content as a whole, identifying relationships between pieces of information, drawing conclusions, and grasping implied information in texts. Furthermore, the reading comprehension learning process has not yet fully engaged students in critical thinking and problem-solving activities. This study aims to determine the effect of the Problem Based Learning (PBL) model assisted by sequential picture media on the narrative text reading comprehension ability of fourth-grade elementary school students. This research employs a quantitative approach using a Quasi-Experimental Design method with a Nonequivalent Control Group Design. The research sample consisted of 31 fourth-grade students from SDN 2 Gunungbatu as the experimental group and 28 fourth-grade students from SDN Pasirangin as the control group. Data were collected using reading comprehension ability tests through Pretest  and Posttest. Data analysis was conducted using normality tests, homogeneity tests, Independent Sample t-Test, and N-Gain tests. The results indicate that there is a significant effect of the Problem Based Learning model assisted by sequential picture media on students' narrative text reading comprehension ability. The Independent Sample t-Test yielded a Sig. (2-tailed) value of < 0.001 < 0.05, leading to the rejection of H₀ and acceptance of H₁. The N-Gain test results showed an average improvement of 74.76% for the experimental group (high category) and 46.27% for the control group (moderate category). Thus, the Problem Based Learning model assisted by sequential picture media is effective in improving the narrative text reading comprehension ability of fourth-grade elementary school students.